Optimal Timing of Simethicone Supplement for Bowel Preparation: A Prospective Randomized Controlled Trial. (27th October 2021) - Wu, Zhen-wen; Zhan, Sheng-gang; Yang, Mei-feng; Meng, Yi-teng; Xiong, Feng; Wei, Cheng; Li, Ying-xue; Zhang, Ding-guo; Xu, Zheng-lei; Wu, Ben-hua; Shi, Rui-yue; Yao, Jun; et al.
Abstract : Background and Aims . Simethicone (SIM), as an antifoaming agent, has been shown to improve bowel preparation during colonoscopy. However, the optimal timing of SIM addition remained undetermined. We aimed to investigate the optimal timing of SIM addition to polyethylene glycol (PEG) to improve bowel preparation. Methods . Eligible patients were randomly assigned to two groups: the SIM evening group (SIM addition to PEG in the evening of the day prior to colonoscopy) and the SIM morning group (SIM addition to PEG in the morning of colonoscopy). The primary outcome was Bubble Scale (BS). The secondary outcomes were Boston Bowel Preparation Scale (BBPS) and adenoma detection rate (ADR). Results . A total of 419 patients were enrolled in this study. The baseline characteristics of the patients were similar in both groups. No significant differences were observed in terms of BS (8.76 ± 0.90 vs. 8.65 ± 1.16, P = 0.81), ADR (34.1% vs. 30.8%, P = 0.47), Boston Bowel Preparation Scale (BBPS) (8.59 ± 0.94 vs. 8.45 ± 1.00, P = 0.15), and withdrawal time (8.22 ± 2.04 vs. 8.01 ± 2.51, P = 0.094) between the two groups. Moreover, safety and compliance were similar in both groups. However, the SIM evening group was associated with shorter cecal intubation time (3.80 ± 1.81 vs. 4.42 ± 2.03, P < 0.001), higher BS (2.95 ± 0.26 vs. 2.88 ± 0.38, P = 0.04) in the right colon, and diminutive ADR (62.5% vs. 38.6%, P = 0.022) in the right colon, when compared to the SIM evening group. Conclusions . The SIM addition to PEG in the evening of the day prior to colonoscopy can shorten cecal intubation time and improve BS scores and diminutive ADR of the right colon compared with the SIM addition to PEG in the morning of colonoscopy in bowel preparation.